PENJADWALAN PRODUKSI DENGAN PENDEKATAN METODE NAWAZ, ENSCORE, HAM (NEH) DAN METODE CAMPBELL, DUDEK, SMITH - Sutanto, Lorens Handy (Industrial and Systems Engineering Assessment Journal (INASEA), 2008)
Companys current scheduling condition is not optimal since too much additional time/work days exists. Planning and creating a better production scheduling system is needed to minimize production time and reduce the additional time. The CDS scheduling method will find the best makespan by combining existing work stations into two groups of machines. Those two groups are sorted by prioritizing on fastest process time, and then the makespan can be created. Meanwhile the NEH scheduling method looks for the makespan by sorting based on the SPT (Shortest Processing Time) first and then enter the job based on the sequence of each. This research found that the NEH scheduling method is the most appropriate since it obtained a bigger cost saving and eliminates overtime.